Case Report: Phototherapeutic Keratectomy for Band Keratopathy Secondary to Chemo-Laser-Cryotherapy for Retinoblastoma - Wei, Ruoyan; Li, Meiyan; Yang, Weiming; Xu, Haipeng; Choi, Joanne; Zhou, Xingtao (Frontiers in Medicine, 2021)
PURPOSE: To report the clinical outcomes of phototherapeutic keratectomy (PTK) for pediatric band keratopathy after treatment for retinoblastoma. METHODS: A 5-year-old boy presented with a 2-year history of poor visual acuity and a horizontal gray-white band across the central cornea in the right eye. He was diagnosed with band keratopathy after chemo-laser-cryotherapy for retinoblastoma. The band keratopathy was treated via PTK using the Mel-90 excimer laser with an optical treatment zone of 7.0 mm and ablation depth of 120 μm. The patient was followed at 1 week and 3 months postoperatively. RESULTS: Surgery and postoperative follow-up were uneventful. At the 3-month follow-up, the uncorrected distant visual acuity of the right eye improved to 20/125, and the corrected distance visual acuity improved to 20/70 with a refraction of +10.00 DS/-2.50 DC×15. The clarity of the ablated area was evidently improved. The central corneal thickness decreases from 612 μm to 584 μm. The optical coherence tomography showed the thin band of hyperreflectivity in the ablated area disappeared, corneal transparency improved and the corneal surface smoothened. CONCLUSIONS: PTK is a safe and effective procedure to treat band keratopathy following treatment of retinoblastoma in children. Early intervention can reduce the risk of developing deprivation amblyopia.